2016
DOI: 10.1021/acs.jnatprod.6b00345
|View full text |Cite
|
Sign up to set email alerts
|

Chemodiversity of Ladder-Frame Prymnesin Polyethers in Prymnesium parvum

Abstract: Blooms of the microalga Prymnesium parvum cause devastating fish kills worldwide, which are suspected to be caused by the supersized ladder-frame polyether toxins prymnesin-1 and -2. These toxins have, however, only been detected from P. parvum in rare cases since they were originally described two decades ago. Here, we report the isolation and characterization of a novel B-type prymnesin, based on extensive analysis of 2D- and 3D-NMR data of natural as well as 90% (13)C enriched material. B-type prymnesins la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 28 publications
3
83
2
Order By: Relevance
“…, and 4: [7]), and Δ indicates results from this study. The prymnesins excreted [40] by P. parvum possess some membrane activity that causes gill damage [6][7][8]13]. The gill damage elicits the FATS gill irritant syndrome observed via oxygen consumption and ventilation rate shown here.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…, and 4: [7]), and Δ indicates results from this study. The prymnesins excreted [40] by P. parvum possess some membrane activity that causes gill damage [6][7][8]13]. The gill damage elicits the FATS gill irritant syndrome observed via oxygen consumption and ventilation rate shown here.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, in contrast to the results obtained in this study that ranged from 1.28 to 24.80 h). In the case of P. parvum, studies showed that each strain of P. parvum likely produces slightly different types and amounts of prymnesins (A-, B-, and C-types), which are the substances suspected to be responsible for the ichthyotoxicity of P. parvum blooms [40]. This could explain why different strains of P. parvum express different toxicities [9] and could be the reason for the discrepancy between the results reported in this study (strain: UTEX-2797) and those previously reported by Bergmann et al [41] for an unknown strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the toxic metabolites responsible for bloom toxicity are not established in Heterosigma akashiwo , making studies of viral impact on toxicity difficult. On the other hand, reports of toxic P. parvum metabolites are numerous and include fatty acids [48], glycerolipids [49] and very large ladder-frame polyether toxins, known collectively as the prymnesins [50,51,52]. Reports of cases of toxic and non-toxic blooms of Prymnesium and other harmful algal species [37] has led to speculation that an ecological trigger exists for toxicity.…”
Section: Discussionmentioning
confidence: 99%